2012
DOI: 10.1177/1468087412458100
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of hydraulic effects of two-stage fuel injection on fuel-injection systems and diesel combustion in a high-speed optical common-rail diesel engine

Abstract: The final, definitive version of this paper has been published in International Journal of Engine Research, Vol 15 Issue 1, September 2012, ppublished by SAGE Publishing, All rights reserved.In order to meet the ever more stringent emission standards, significant efforts have been devoted to the research and development of internal combustion engines. The requirements for more efficient and responsive diesel engines have led to the introduction and implementation of multiple injection strategies. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…It is important to note that there exists a time lag between the start of the injector current waveform and the start of fuel injection due to the inertia of the system as illustrated in Figure 4. The authors have previously reported on the hydraulic effects of two-stage injection on fuel injection quantity, combustion characteristics and emissions [24,25]. It was identified that the fuel injection quantity during the second injection was substantially influenced by the first injection when they were closely spaced in time.…”
Section: Metal -Soot Emissionsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that there exists a time lag between the start of the injector current waveform and the start of fuel injection due to the inertia of the system as illustrated in Figure 4. The authors have previously reported on the hydraulic effects of two-stage injection on fuel injection quantity, combustion characteristics and emissions [24,25]. It was identified that the fuel injection quantity during the second injection was substantially influenced by the first injection when they were closely spaced in time.…”
Section: Metal -Soot Emissionsmentioning
confidence: 99%
“…The fuel injection rate profiles of the twin and variable split fuel injection strategies are presented in Figure 5. It should be noted that the twin split injections were obtained with the same energising time for the first and second injections and the difference in the fuel injection quantity in the second injection was mainly attributed to the design limitations of the injector utilised as well as the adverse effects of pressure waves in the high pressure fuel line, caused by the first injection [24,25]. Consequently, the FIE was thoroughly calibrated and the second fuel injection pulse width was optimised such that the quantity of fuel injected during the second injection was identical to that of the first injection, Figure 5 and Table 5.…”
Section: Metal -Soot Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain the gain curves of the injector utilised, injection rate and quantity of single injection strategies as a function of injection pulse width and injection pressure were experimentally evaluated using a FIE calibration test rig based on Zeuch's method presented by Ishikawa et al [34]. Detailed explanation of the experimental setup/procedure can be found in [35,36]. Several single injection strategies with different injection duration were tested at the injection pressure of 1200 bar in order to evaluate the fuel injection quantity as a function of injection pulse width, Figure 6.…”
Section: Operating Conditionsmentioning
confidence: 99%